Extracorporeal membrane oxygenation for adult respiratory distress syndrome in trauma patients: A case series and systematic literature review. Issue 1 (January 2017) - Robba, Chiara; Ortu, Andrea; Bilotta, Federico; Lombardo, Alessandra; Sekhon, Mypinder S.; Gallo, Fabio; Matta, Basil F.
Abstract : BACKGROUND: Venovenous extracorporeal membrane oxygenation (vv-ECMO) is an established salvage therapy for severe respiratory failure, and may provide an alternative form of treatment for trauma-induced adult respiratory distress syndrome (ARDS) when conventional treatments have failed. The need for systemic anticoagulation is a relative contraindication for patients with bleeding risks, especially in multitraumatic injury. METHODS: We describe a case series of four trauma patients with ARDS who were managed with ECMO admitted to the neuro critical care unit at Addenbrooke's Hospital, Cambridge (UK), from January 2000 to January 2016. We performed a systematic review of the available literature to investigate the safety and efficacy of vv-ECMO in posttraumatic ARDS, focusing on the use of different anticoagulation strategies and risk of bleeding on patients with multiple injuries. RESULTS: Thirty-one patients were included. A heparin bolus was given in 16 cases. Eleven patients developed complications during treatment with ECMO with three cases of major bleeding. In all documented cases of bleeding a bolus and infusion of heparin was administered, aiming for an activated clotting time (ACT) target longer than 150 seconds. Two patients treated with heparin-free ECMO developed thromboembolic complications. Four patients died, and death was never directly or indirectly related to use of ECMO. CONCLUSION: vv-ECMO can be lifesaving in respiratory failure. Our experience and our literature review suggest that vv-ECMO should be considered as a rescue treatment for the management of severe hypoxemic respiratory failure secondary to ARDS in trauma patients. For patients with a high risk of bleeding, the use of ECMO with no initial anticoagulation could be considered a valid option. For patients with a moderate risk of bleeding, use of a heparin infusion keeping an ACT target shorter than 150 seconds can be appropriate. LEVEL OF EVIDENCE: Therapeutic study, level V.